2021
DOI: 10.3390/ma15010139
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method for Apples’ Bruise Area Prediction

Abstract: From the producers’ point of view, there is no universal and quick method to predict bruise area when dropping an apple from a certain height onto a certain type of substrate. In this study the authors presented a very simple method to estimate bruise volume based on drop height and substrate material. Three varieties of apples were selected for the study: Idared, Golden Delicious, and Jonagold. Their weight, turgor, moisture, and sugar content were measured to determine morphological differences. In the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The flesh hardness at a depth of 25 mm was 0.58272 N/mm 2 . The source of the hardness measurement method was compared with the method of Słupska et al [31,32]. The mechanical structure of the apple was different from that of a uniformly textured rubber ball.…”
Section: Structural and Distributive Mechanical Properties Of Applesmentioning
confidence: 99%
“…The flesh hardness at a depth of 25 mm was 0.58272 N/mm 2 . The source of the hardness measurement method was compared with the method of Słupska et al [31,32]. The mechanical structure of the apple was different from that of a uniformly textured rubber ball.…”
Section: Structural and Distributive Mechanical Properties Of Applesmentioning
confidence: 99%
“…The artificial intelligence model has high precision, wide applicability and high-fault tolerance, and has been widely used to predict the quality and chemical properties of other fruits. For example, Słupska et al [29] used a linear regression model (R 2 = 0.93) to predict the damage area of apples under impact load, while the R 2 values of the three models presented in this paper were greater than 0.98. In particular, for the ANFIS model, Vesely et al [30] found that in other aspects of forecasting, specifically, the fuzzy logic model compared to the traditional linear regression model, should be used by other scholars.…”
Section: Discussionmentioning
confidence: 86%
“…Experiments that involve striking a fruit placed at the end of an arm against a flat surface [ 17 , 18 , 19 , 20 , 21 ] or striking an immobile fruit with an impactor fixed to the pendulum [ 22 , 23 , 24 ] are more frequently applied. Another type of test involves free dropping from a chosen height; this is used for estimations of the fruit’s characteristics, e.g., guava ripeness [ 25 ] or apples’ resistance to damages [ 26 ]. Such investigations have determined the results of loads during the impact of various materials against surface areas [ 27 ] and the elasticity modulus and maximal forces using a triaxial acceleration sensor for potato tubers [ 28 ].…”
Section: Introductionmentioning
confidence: 99%